Natural origin polymer-based nanocarriers as tools for controlled release of bioactive factors aimed to manipulate stem cells performance in bone and cartilage tissue regeneration strategies - Santo, Vítor Sérgio Soares Espírito (2012)
Programa doutoral em Engenharia de Tecidos, Medicina Regenerativa e Células Estaminais